A flume test of a model net with varying wing-end widths to characterize the performance of shrimp trawl in Kotabaru, Indonesia - Ahmadi, . (Journal of Fisheries, 2018)
Shrimp trawl net is the prominent fishing gear that beneficially supports shrimp industries in Kotabaru, Indonesia. However, concurrently local fishermen have no idea how trawl works under towing condition. For this reason, a flume test of a 1/8 scale model net with varying wing-end widths was undertaken. The flow speeds of model were 48, 56, 64, 72, and 80 cm s–1. Meanwhile wing tips distance was set at 46–66% of head-rope length. At a towing speed of 64 cm s–1 (2-knot in full scale), the net height was 12 cm, the projective area of net mouth was 9.16×102 cm2, water filtering volume was 58.44×103 cm3 s–1 and total net resistance was 6.34×102 g. The ratios of net height to net circumference ranged of 0.04–0.08. The net height was 5.5% of net circumference and getting lower at higher towing speeds. The exponent value of 1.40 was smaller than the suggested value (2.0) indicating the shape of net body should be refined by inserting triangle nets between the side net and baiting. Moreover, the length of nets should be afforded to the lacing lines to increase the height of net opening by better distributing the towing forces.